Assessment of Modification of Diet in Renal Disease Equation to Predict Reference Serum Creatinine Value in Severe Trauma Patients: Lessons From an Observational Study of 775 Cases. Issue 4 (April 2016) - Saour, Marine; Klouche, Kada; Deras, Pauline; Damou, Asmaa; Capdevila, Xavier; Charbit, Jonathan
Abstract : Objective: We assessed the Modification of Diet in Renal Disease (MDRD) performance to predict serum creatinine (SCr) in severe trauma population and determined the best theoretical glomerular filtration rate (GFR) to use in this estimation. Background: Baseline SCr may be misestimated in severe trauma patients because of their specific demographic characteristics including renal hyperfiltration. However, the back-calculated MDRD equation is supposed to estimate SCr using a predetermined GFR of 75 mL/min/1.73 m 2 . Methods: All severe trauma patients with a normal SCr were retrospectively included between January 2005 and January 2011. For each patient, the lowest SCr (oSCr) observed during the first week was used to estimate the GFR. The median GFR in period 1 (2005–2006) was determined. The back-calculated MDRD performance was assessed in period 2 (2007–2011) to predict oSCr by agreement, precision, and accuracy using a GFR of 75 mL/min/1.73 m 2 ( eSCr 75 -MDRD) or the median GFR observed in period 1 ( eSCr TRAUMA -MDRD). Results: A total of 775 patients were studied: mean age, 37.7 ± 17 years; mean Injury Severity Score, 19 ± 11; 75% of male. In period 1 (n = 243), median GFR was 121 mL/min/1.73 m 2 . In period 2 (n = 532), eSCr TRAUMA -MDRD demonstrated better agreement in predicting oSCr than eSCr 75 -MDRD (mean bias 2 vs 35 μmol/L; P < 0.001). Both precision (14 vs 39 μmol/L, respectively) and accuracy were significantly improved with eSCr TRAUMA -MDRD. Proportion of estimated SCr values that deviated less than 15%, 30%, or 50% was also higher with eSCr TRAUMA -MDRD ( P < 0.001). Conclusions: The eSCr 75 -MDRD equation systematically overestimates oSCr of severe trauma patients. The eSCr TRAUMA -MDRD equation determined was statistically superior allowing more accurate qualification of acute kidney injury.